2011
DOI: 10.1136/bmjqs-2011-000300
|View full text |Cite
|
Sign up to set email alerts
|

Do older patients' perceptions of safety highlight barriers that could make their care safer during organisational care transfers?

Abstract: BackgroundHealthcare is a series of complex, interwoven systems in which any discontinuities of care may affect the safety of patients, who have been reported to perceive safety differently to clinicians. This study aimed to explore patient perceptions of safety and identify how they can be used to construct additional barriers to reduce safety incidents within organisational care transfers, which are known to be high in risk.DesignAppreciative Inquiry (AI) methodology was used to develop semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…In recent years it has been argued that patients in acute and general healthcare settings have the potential to act as safety buffers by voicing concerns and pre-empting failures in care 10 32 33. Our analysis shows that women using maternity services also demonstrate this ability.…”
Section: Discussionmentioning
confidence: 65%
“…In recent years it has been argued that patients in acute and general healthcare settings have the potential to act as safety buffers by voicing concerns and pre-empting failures in care 10 32 33. Our analysis shows that women using maternity services also demonstrate this ability.…”
Section: Discussionmentioning
confidence: 65%
“…As identified earlier, there is an increasing emphasis on the need for patients to be involved in their own safety,13 14 37 highlighted by the recent events and subsequent enquiries at Mid-Staffordshire NHS Foundation Trust 16 17. This need can be addressed through patient reporting of safety concerns or incidents,30 so that organisations can learn from the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The questions asked in each stage of the care transfer are provided in table 1, and focus around six domains: communication , responsiveness , waiting times , falls , medication and hygiene . These domains are based on patient perceptions of safety 14. Patients or their carers are asked to report on three levels of safety: safe (green), neutral (yellow) and unsafe (red), and to leave any non-applicable sections blank.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a study of patients' definitions of safety and harm in transitions of care, older people reported feeling unsafe during their transfers of care if not clearly communicated with (Scott, Dawson, and Jones 2012). Alongside the more traditional risks to patient safety such as falls, medication concerns, and health care acquired infections, the authors of this study suggested that an excess of trust of a patient in the clinical professionals treating him could act as a 'latent condition' that actually reduces the patient's ability to be involved in his safety.…”
Section: Patient Perceptions Of Safety and Experiences Of Raising Conmentioning
confidence: 98%
“…Alongside the more traditional risks to patient safety such as falls, medication concerns, and health care acquired infections, the authors of this study suggested that an excess of trust of a patient in the clinical professionals treating him could act as a 'latent condition' that actually reduces the patient's ability to be involved in his safety. Improved communication, to provide a more solid foundation for trust and challenge between patient and clinician and ensure responsiveness to the patient's individual needs, was thus proposed as an additional safety step (Scott, Dawson, and Jones 2012). Entwistle et al (2010), too, highlight the importance of the way in which safety concerns are received by professionals in shaping the extent to which patients feel comfortable about 'speaking up' about safety concerns and call for a dual strategy, which encourages both patients to speak up and staff to listen to them.…”
Section: Patient Perceptions Of Safety and Experiences Of Raising Conmentioning
confidence: 99%